Exploring proxies for occupation intensity in hunter-gatherer settlement systems: A combination of ethnohistoric and archaeological data - Amy E. Clark; Guadalupe Sánchez Miranda; Neftalí López-Pérez; Antonio López-Rivera; Tamara Luna; Astrid Avilés; Richard Martynec; Sandra Martynec; Natalia Martínez-Tagüeña; Matthew Pailes (PLoS ONE, 2025)
A primary concern for hunter-gatherer archaeology is whether occupation intensity can be broken down into its constituent components: group size, length of stay(s), and frequency of reoccupation. This article contributes to this discussion with settlement pattern data from the traditional homeland of the Hia-Ced O’odham. We employ multiple material proxies of occupation intensity in addition to site area. Our approach highlights that patterns produced by logistically mobile systems with significant levels of site reuse present unique obstacles that contrast with the residentially mobile systems that underpin much current discussion and most ethnographic baselines. We provide one simple measure for identifying the relative magnitude of site reuse in settlement pattern data. Our multiple proxy landscape scale analysis also allows us to move beyond broad characterizations of economic strategies and identify site specific roles and strategies within larger settlement systems. Rather than viewing sites with anomalous relationships between proxies as problematic, they provide an avenue for identifying unique components of settlement systems and the impact of social negotiations intrinsic to human landscape use.